Features of Family Proceedings - Yesayan, Vard (Bulletin of Yerevan University C: Jurisprudence, 2024)
Family proceedings represent a novel addition to the procedural legislation of Armenia, and within civil proceedings, this proceeding is categorized as a special claim proceeding. The legislator, in the context of these proceedings, has underscored the importance of safeguarding the best interests of the child and has outlined specific features of the examination. This article discusses the distinctive characteristics of family cases within this framework. Within the scope of this article, family cases are conventionally grouped into three main categories: Family cases based on family legal relations. Family affairs based on the best interests of the child. Family cases concerning the return of a child illegally transferred to the Republic of Armenia or illegally kept in the Republic of Armenia.